Long non-coding RNA GRASLND links melanoma differentiation and interferon-gamma response - Fischer, Kim Denise; Tiwari, Shashank; Thier, Beatrice; Qiu, Lin Christina; Lin, Tzu-Chen; Paschen, Annette; Imig, Jochen (Frontiers in Molecular Biosciences, 2024)
Melanoma is a highly malignant tumor, that stands as the most lethal form of skin cancer and is characterized by notable phenotypic plasticity and intratumoral heterogeneity. Melanoma plasticity is involved in tumor growth, metastasis and therapy resistance. Long non-coding RNAs (lncRNAs) could influence plasticity due to their regulatory function. However, their role and mode of action are poorly studied. Here, we show a relevance of lncRNA GRASLND in melanoma differentiation and IFNγ signaling. GRASLND knockdown revealed switching of differentiated, melanocytic melanoma cells towards a dedifferentiated, slow-proliferating and highly-invasive cell state. Interestingly, GRASLND is overexpressed in differentiated melanomas and associated with poor prognosis. Accordingly, we found GRASLND expressed in immunological “cold” tumors and it negatively correlates with gene signatures of immune response activation. In line, silencing of GRASLND under IFNγ enhanced the expression of IFNγ-stimulated genes, including HLA-I antigen presentation, demonstrating suppressive activity of GRASLND on IFNγ signaling. Our findings demonstrate that in differentiated melanomas elevated expression of GRASLND interferes with anti-tumor effects of IFNγ, suggesting a role of GRASLND in tumor immune evasion.